PROCESSING OF COCONUTS INTO VIRGIN COCONUT OIL (VCO) AS AN EFFORT FOR AGRICULTURAL PRODUCT DIVERSIFICATION IN VILLAGES: PENGOLAHAN KELAPA MENJADI VIRGIN COCONUT OIL (VCO)SEBAGAI UPAYA DIVERSIFIKASI PRODUK PERTANIAN DI DESA - Baihaqi; Ika Rezvani Aprita; Sri Agustina; Muhammad Rahmad Ramadhan; Windayani; Harmiaty Bahar; Abdi Juryan Ladianto (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2025)
The production of Virgin Coconut Oil (VCO) in rural areas represents an effort to diversify agricultural products, which can improve the welfare of local communities by utilizing coconut as a regional natural resource. VCO offers numerous health benefits, such as boosting the immune system,  lowering cholesterol, and containing high levels of antioxidants. This community service program aims to provide the local population with the knowledge and practical skills on how to produce VCO properly. The methodology includes socialization, technical training, evaluation, and follow-up assistance. The pre- and post-test evaluation results show a significant improvement in participants' knowledge and skills. Approximately 85% of the participants understood the process of making VCO after the training, indicating the program's effectiveness. Furthermore, this initiative has opened new economic opportunities, with several participants beginning to produce and sell VCO independently. The main challenges faced include limited capital and market access. However, with continuous support and assistance from various stakeholders, this program is expected to further develop. The production of VCO presents a promising alternative to increase the income of rural communities and reduce dependence on a single agricultural commodity